A Particular Collection of Service Time Distributions Parameters Study and Impact in some MGinf System Busy Period and Busy Cycle Parameters - Ferreira, M. A. M. (arXiv:2110.03454, 2025)
The problems arising when the moments of service time distributions, for which the MGinf queue system busy period and busy cycle become very easy to study, are presented and it is shown how to overcome them. The busy cycle renewal function and the peakedness and the modified peakedness for the MGinf busy period and busy cycle in the case of those service time distributions are also computed.